اصلاحِ اخلاق و کردار میں صوفیہ کا کردار: فکرِ باہو کا مطالعہ (Al-Qamar, 2020)
Sufis have played a remarkable role in efforts to reform morality and character. This article studies the thought of Sultān Bāhū, a prominent Sufi of 17the century, on moral and character building of human beings. It finds that the referred Sufi played a pivotal role in moral and character building of his followers as well as all seekers of high moral ranks. It ends with the suggestion of adopting Bāhū’s thought to equip the individuals and society with good manners.
Keywords: Sufi thought; morality; Sultān Bāhū